Rubella Vaccination of Unknowingly Pregnant Women: The Sao Paulo Experience, 2001 - Sato, Helena K.; Sanajotta, Andrea Torres; Moraes, Jose Cassio; Andrade, Joelma Queiroz; Duarte, Geraldo; Cervi, Maria Celia; Curti, Sueli P.; Pannuti, Claudio Sergio; Milanez, Helaine [UNESP]; Pessoto, Monica [UNESP]; Flannery, Brendan; Oselka, Gabriel W. (Oxford Univ Press Inc, 2011)
Background. Rubella vaccination is contraindicated during pregnancy. During mass immunization of women of childbearing age against rubella, women unknowingly pregnant may be vaccinated. To evaluate the effects of rubella vaccination during pregnancy, the Brazilian state of Sao Paulo conducted a follow-up study of pregnant women vaccinated during a rubella campaign in 2001.Methods. Women vaccinated during pregnancy were reported to a national surveillance system. In the state of Sao Paulo, follow-up of vaccinated women included household interviews. Serum samples from vaccinated women were tested for antirubella antibodies to classify susceptibility to rubella infection. Children born to susceptible mothers were tested for evidence of congenital rubella infection and evaluated for signs of congenital rubella syndrome.Results. The Sao Paulo State Health Department received 6473 notifications of women vaccinated during pregnancy. Serology performed for 5580 women identified 811 (15%) that were previously susceptible. Incidence of spontaneous abortion or stillbirth among previously susceptible vaccinated women was similar to women with prior immunity. Twenty-seven (4.7%) of 580 newborns tested had evidence of congenital rubella infection; none had congenital rubella syndrome.Conclusions. Mass rubella vaccination of women of childbearing age was not associated with adverse birth outcomes or congenital rubella syndrome among children born to women vaccinated during pregnancy.